Snowball Throwing in Teaching Grammar - apsari, yanuarti (Lingual Journal of Language and Culture; Vol 5 No 1 (2018), 2018)
The aims of this study were to describe the implementation of snowball throwing in teaching grammar and to investigate the benefits of applying snowball throwing. The research was conducted at STKIP Siliwangi Bandung. This study employed qualitative research involving one class consisting of second semester students in English department who were taking the subject of foundation of English grammar. The data were obtained from classroom observation and students’ interview. The findings showed that there are seven stages in implementing snowball throwing in teaching grammar. The stages consist of preparing teaching material, forming group, re-explaining the material to the member of the group, formulating question, tossing the ball, answering questions and evaluating teaching and learning process. In addition, the findings also revealed that there are some benefits from applying snowball throwing in teaching grammar such as improving of students’ comprehension in learning grammar, creating enjoyable learning’s atmosphere, increasing students’ vocabulary mastery, developing students’ speaking skill, developing of students’ cooperation skill and increasing of students’ participation in the class.   Keywords: Snowball throwing; benefits; grammar.